Migrant remittances and dutch disease: evidence from India - Muhammad Faheem; Mohamed Azali; Lee Chin (Faculty of Economics, University of Tehran, 2022)
This study deals with the question of whether the inflow of migrant remittances causes Dutch Disease or not in India. For this purpose, the study employs the Autoregressive Distributed Lag Model (ARDL) to examine the influence of migrant remittances on the real effective exchange rate spanning the period from 1975 to 2018. In the long run, the study finds a positive relationship between migrants’ remittances and the real effective exchange rate, meaning that evidence of Dutch Disease risk in India. The study also checks the moderating effect of inflation on remittances and real effective exchange rate relationship and finds a negative effect. The study recommends that the government of India would implement and design the policies for the diversification of remittances flow toward priority areas of investment.